2015
DOI: 10.1155/2015/961782
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison Simulating Face to Face Endotracheal Intubation of Pentax Airway Scope, C-MAC Video Laryngoscope, Glidescope Video Laryngoscope, and Macintosh Laryngoscope

Abstract: Objectives. Early airway management is very important for severely ill patients. This study aimed to investigate the efficacy of face to face intubation in four different types of laryngoscopes (Macintosh laryngoscope, Pentax airway scope (AWS), Glidescope video laryngoscope (GVL), and C-MAC video laryngoscope (C-MAC)). Method. Ninety-five nurses and emergency medical technicians were trained to use the AWS, C-MAC, GVL and Macintosh laryngoscope with standard airway trainer manikin and face to face intubation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
4
11
0
2
Order By: Relevance
“…Similar to our observations, Choi et al [13] attributes this to the significant hand-eye discordance which appears to occur when the VL is used in this unconventional situation. The finding in our study that use of VL was also associated to an increased risk of failed intubations (RR: 6.4, CI 0.95; 0.92–44.33, p = 0.018) and that of Choi et al [13] suggests that DL remains the technique of choice in the restricted space face-to-face scenario, and VL should not be used in these situations. Our findings also suggest that in the hands of novice prehospital providers VL does not appear offer any additional advantage over DL in the simulated setting for intubation success, although other studies have indicated contradictory findings [11] .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our observations, Choi et al [13] attributes this to the significant hand-eye discordance which appears to occur when the VL is used in this unconventional situation. The finding in our study that use of VL was also associated to an increased risk of failed intubations (RR: 6.4, CI 0.95; 0.92–44.33, p = 0.018) and that of Choi et al [13] suggests that DL remains the technique of choice in the restricted space face-to-face scenario, and VL should not be used in these situations. Our findings also suggest that in the hands of novice prehospital providers VL does not appear offer any additional advantage over DL in the simulated setting for intubation success, although other studies have indicated contradictory findings [11] .…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to this our results in fact indicated the opposite. These findings correlate with that of Choi et al [13] who, at same period of our data collection, conducted a similarly study comparing different VL and DL devices in the restricted space face-to-face intubation scenario. Choi et al [13] reported that intubation time was significantly improved with the use of the DL (Macintosh and Pentax Airway Scope), as compared to the C-MAC and Glidescope VL systems.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sitting endotracheal intubation is a useful technique for airway control, in patients with difficult airway or in patients in whom maintenance of the upright posture is beneficial ( 3 ), such as patients with tracheal compression ( 4 ), or superior vena cava syndrome ( 5 , 6 ). The technique consists of advancing the endotracheal tube to vocal cords of patient in face-to-face position, when patient is in the sitting or semi-sitting position ( 7 ).…”
Section: Introductionmentioning
confidence: 99%